Development of Interactive Learning Media Based on Canva Website for the Customer Service Element in Phase F Grade XI at SMK Negeri 44 Jakarta - Rina Putri Hendryana; Dita Puruwita; Rizka Zakiah (The Future of Education Journal, 2026)
The development of technology in education requires the use of digital media that is interactive and suitable for students’ characteristics. However, learning in the Customer Service element at SMK Negeri 44 Jakarta is still dominated by presentations and lecture methods, so more visual and contextual learning media are needed. This study aims to develop interactive learning media based on Canva Website, determine its feasibility, and examine its effectiveness in learning. The research subjects included material experts, media experts, instructional design experts, and Grade XI Retail Business students at SMK Negeri 44 Jakarta. Data were collected through observation, expert validation questionnaires, and tests in the form of pretest and posttest. The data analysis techniques used were feasibility percentage analysis and N-Gain calculation. The validation results showed that the material expert obtained a percentage of 80% in the feasible category, the media expert obtained 85% in the highly feasible category, and the instructional design expert obtained 87.69% in the highly feasible category. The average validation result reached 84.23%, which was categorized as highly feasible. The effectiveness test on the service excellent material showed an average pretest score of 62.83 and an average posttest score of 78.13, with an average N-Gain of 0.41 in the moderate category. Based on these results, the interactive learning media based on Canva Website was declared highly feasible and fairly effective for use in Customer Service learning.